Pluralitas Dalam Teori Perencanaan - Rina Priyani (The Institute for Research and Community Services, Institut Teknologi Bandung, 2007)
Pluralism is nothing new but plurality approach in planning theory is a recent reaction to the failture of rational comprehensive planning. Planning itself is considered to be